Sufi Rhetoric in Khithobah(An Analysis of the Rhetoric of Syekh Abdul Qodir Jailani’s Khithobah to a Specific Audience) - Dadang Muliawan; Yufi Mohammad Nasrullah; Nurul Fatonah; Fiqra Muhamad Nazib; Mohd Noor bin Mohd (Mauriduna : Journal of Islamic Studies, 2025)
Assertiveness in Islamic preaching is a crucial aspect in preserving the purity of religious principles and moral boundaries, particularly in the face of modern challenges that emphasize inclusivity. This study aims to analyze the rhetorical strategies employed by Shaykh Abdul Qadir al-Jilani in delivering Sufi-oriented sermons that combine firmness with spiritual depth. Using a qualitative method with a rhetorical discourse analysis approach, this research draws on sermon texts and historical literature as primary data sources. The findings reveal that Shaykh Abdul Qadir al-Jilani incorporates the classical rhetorical elements of ethos, pathos, and logos in his preaching: ethos to establish credibility, pathos to evoke emotional responses from the audience, and logos through arguments grounded in the Qur'an and Hadith. His rhetoric demonstrates a balance between sharp criticism of moral deviations—particularly among scholars and rulers—and compassionate counsel to sinners, emphasizing repentance and sincerity. The Sufi dimension is evident in his use of symbolic language and narratives of spiritual experiences that encourage deep reflection and connect religious teachings with social well-being. These findings indicate that Shaykh Abdul Qadir al-Jilani’s rhetorical approach remains relevant for contemporary Islamic preaching, particularly in striking a balance between moral assertiveness and empathetic communication. Further research is recommended to explore the impact of this approach in modern contexts and to compare it with other Sufi figures.